A Naphthalimide-Based Fluorescence “Off-on-Off” Chemosensor for Relay Detection of Al3+ and ClO− - Sun, Xue-Jiao; Liu, Ting-Ting; Fu, Hong; Li, Na-Na; Xing, Zhi-Yong; Yang, Fan (Frontiers in Chemistry, 2019)
A novel Al3+ chemosensor NPA was designed and synthesized on basis of the mechanism of ICT and CHEF. Upon addition of Al3+, the probe NPA displayed a bright green fluorescence under UV radiation and visual color change from yellow to colorless. Spectrum titrations showed that NPA could be recognized as a fluorescent turn-on probe with 10-8 M detection level. The probe was successfully applied in real water sample and test paper. More important, NPA-Al3+ complex were used as a fluorescent turn-off probe for the detection of ClO- with the detection as low as 2.34×10-8 M. The performance of of NPA to Al3+ and NPA-Al3+ complex to ClO- demonstrated that NPA could be served as a sensitive probe and exhibit INHIBIT logic gate behavior with Al3+ and ClO- as inputs.